2013
DOI: 10.1017/jfm.2012.606
|View full text |Cite
|
Sign up to set email alerts
|

The role of wake stiffness on the wake-induced vibration of the downstream cylinder of a tandem pair

Abstract: When a pair of tandem cylinders is immersed in a flow the downstream cylinder can be excited into wake-induced vibrations (WIV) due to the interaction with vortices coming from the upstream cylinder. Assi, Bearman & Meneghini (J. Fluid Mech., vol. 661, 2010, pp. 365-401) concluded that the WIV excitation mechanism has its origin in the unsteady vortex-structure interaction encountered by the cylinder as it oscillates across the wake. In the present paper we investigate how the cylinder responds to that excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 27 publications
9
51
1
1
Order By: Relevance
“…At the two closest distances, all three shapes show signs of wake induced response similar to trends reported in the literature for cylinders in tandem at similar distances: d x /d = 2 to 5.6 (Hover & Triantafyllou 2001;Assi et al 2006Assi et al , 2010Assi et al , 2013. The circular cylinder vibrates at roughly similar amplitudes in the wake as it does in open water (except at the closest distance).…”
Section: Effects Of Distance and Geometrysupporting
confidence: 81%
See 1 more Smart Citation
“…At the two closest distances, all three shapes show signs of wake induced response similar to trends reported in the literature for cylinders in tandem at similar distances: d x /d = 2 to 5.6 (Hover & Triantafyllou 2001;Assi et al 2006Assi et al , 2010Assi et al , 2013. The circular cylinder vibrates at roughly similar amplitudes in the wake as it does in open water (except at the closest distance).…”
Section: Effects Of Distance and Geometrysupporting
confidence: 81%
“…The upstream cylinder continues to have significant effect on the downstream cylinder's response when the two are of unequal diameter and at relatively small distances apart (Sayers & Saban 1994;Lam & To 2003;Assi 2014b;Gao et al 2014). It was also found that a 'wake stiffness' exists -that is, the vortical wake of the upstream cylinder causes a restoring force on the downstream cylinder, which is equivalent to a linear spring, hence affecting its natural frequency (Assi et al 2013). No studies for large distances are available.…”
Section: Introductionmentioning
confidence: 99%
“…At the two closest distances, all three shapes the cylinder, the elliptical cylinder, and the whisker show signs of wake induced response, which is similar to trends reported in the literature for cylinders in tandem at similar distances d x /d = 2 to 5.6 [65,5,4,3].…”
Section: Comparison Between the Whisker And The Cylinder And Ellipticsupporting
confidence: 86%
“…This is a new result, which is different from the case of two interacting cylinders of comparable diameter, wherein the downstream flexibly mounted cylinder oscillates at a frequency determined by its mass and spring properties, the value of the added mass, and the wake spring constant of the wake defined in [3]. In the case of a stationary upstream cylinder with significantly larger diameter than the downstream body (2.5x, 4x, and 11x in our experiments), the flexibly mounted downstream body vibrates freely at the Strouhal frequency of the upstream cylinder, following a path that slaloms among the vortices of the oncoming wake.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation